Investigating Japan’s physical education assistance to other countries: extraction of major categories and examination of their relevance - Tomoya Shiraishi (Journal of International Cooperation in Education)
Purpose – This study aims to provide the history and overview of the major categories of physical education (PE) assistance that Japan has provided to other countries by extracting the major categories from the various materials. Design/methodology/approach – This study is divided into two phases, Phases 1 and 2. Surveys and analyses were further conducted. In Phase 1, a web browser-based survey was conducted to ascertain the major categories of PE assistance that Japan has provided to other countries. The practices and projects investigated were classified inductively, and the major categories were extracted. In Phase 2, a literature review was conducted to organise the history and overview of each category extracted in Phase 1. Findings – Six major categories were extracted: (1) dispatch of Japan Overseas Cooperation Volunteers engaged in PE assistance, (2) assistance through training for those involved in PE, (3) revision or formulation of a PE curriculum, (4) preparation of textbooks or instructional materials for PE, (5) organising sports event and (6) maintenance of PE equipment and facilities. Originality/value – Japan has a long history of providing PE assistance to other countries. However, historical materials on the practices and projects of PE are becoming scattered. Little literature addresses this gap, which this study seeks to address. This study can help policy makers in other countries, who can use Japan’s PE assistance practices and policies for reference, to assist them in formulating their own policies.